A Subunit of ESCRT-III, MoIst1, Is Involved in Fungal Development, Pathogenicity, and Autophagy in Magnaporthe oryzae - Sun, Lixiao; Qian, Hui; Wu, Minghua; Zhao, Wenhui; Liu, Mengyu; Wei, Yunyun; Zhu, Xueming; Li, Lin; Lu, Jianping; Lin, Fucheng; Liu, Xiaohong (Frontiers in Plant Science, 2022)
The culprit of rice blast, Magnaporthe oryzae, is a filamentous fungus that seriously affects the yield and quality of rice worldwide. MoIst1, a subunit of ESCRT-III, is involved in identified ubiquitinated proteins and transports them into the intraluminal vesicles of MVBs for degradation in lysosomes. Here, we identify and characterize MoIst1 in M. oryzae. Disruption of MoIst1 leads to a significant decrease in sporulation and formation of appressoria, defects in response to oxidative stress, cell wall stress, hyperosmotic stress, and reduced pathogenicity. Deletion of MoIst1 leads to decreased Pmk1 phosphorylation levels and appressorium formation due to the delayed translocation and degradation of lipid droplets and glycogen, resulting in a decreased appressorium turgor. MoIst1 is also involved in the response to hyperosmotic stress. In addition, deletion of MoIst1 leads to an abnormal autophagy and ER-phagy. In summary, our results indicate that MoIst1 is involved in sporulation, appressorium development, plant penetration, pathogenicity, autophagy, and ER-phagy in M. oryzae.